2021
DOI: 10.3390/agronomy11050833
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Vermicomposting System Provides More Efficient Wastewater Use of Dairy Farms Using Eisenia fetida

Abstract: Dairy cattle farming produces large amounts of wastewater and it causes environmental pollution and eutrophication of rivers, but the nutrients in the waste could be recycled. Here, an improved vermicomposting system was applied to dairy farm wastewater, and wastewater with a nitrogen content of 100 mg/L and 200mg/L tested with different combinations of organic substrates such as cow manure and rice straw in rural solid waste. Results showed that earthworms could continuously grow, wastewater (N 100mg/L) mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The results also showed that the highest concentration of P was seen in 10% v/v rice husk when treated by vermicomposting (RH10+EW) (Table 3). These results are consistent with the findings of Liu et al [39]. They observed that vermicomposting significantly changed physicochemical parameters of wastewater in nutrients, such as the percentages of total nitrogen, phosphorous, and potassium, which were found to increase during vermicomposting.…”
Section: Total Nitrogen (N) and Phosphorous (P)supporting
confidence: 93%
“…The results also showed that the highest concentration of P was seen in 10% v/v rice husk when treated by vermicomposting (RH10+EW) (Table 3). These results are consistent with the findings of Liu et al [39]. They observed that vermicomposting significantly changed physicochemical parameters of wastewater in nutrients, such as the percentages of total nitrogen, phosphorous, and potassium, which were found to increase during vermicomposting.…”
Section: Total Nitrogen (N) and Phosphorous (P)supporting
confidence: 93%
“…Liu et al 44 initiated a study involving the earthworm Eisenia fetida was used to remove the dairy waste into a useful product thereby reducing the eutrophication problem. In this experiment various concentration of dairy water mingled with organic waste such as cow dung, rice straw had been used.…”
Section: Food and Fruit Wastementioning
confidence: 99%
“…This observation was used to propose new parameters (i.e., WEN, TOC/WEN) to optimize the composting process. An improved vermicomposting system was proposed to treat dairy wastewater, rice, straw, and cow manure and to recover nutrients [10]. The results of this study showed that this can represent a feasible method for the simultaneous disposal of organic wastes, especially in poor countries, because it incurs lower costs and has a lower impact on the environment.…”
mentioning
confidence: 98%